Human Resource Management Research Trends Based on Total Quality Management (TQM) - Muhamad Akbar (North Press, 2025)
This study aims to explore the research trends and intellectual structure of scholarly publications at the intersection of Human Resource Management (HRM) and Total Quality Management (TQM) using bibliometric analysis. Drawing data from the Scopus database and analyzing it through VOSviewer, the study maps co-authorship networks, co-citation patterns, keyword co-occurrences, and temporal evolution of themes between 2000 and 2024. The results reveal that TQM has progressively evolved from a process- and control-oriented framework into a more human-centered and knowledge-driven paradigm, with HRM functioning as a critical enabler of quality culture, employee development, and organizational effectiveness. Influential authors such as Schroeder, Prajogo, and Sohal emerge as central nodes in the literature, while countries like the United States, India, and Malaysia demonstrate strong international research collaboration. Emerging themes include job satisfaction, personnel training, knowledge management, and sectoral applications in healthcare and education. This study highlights research gaps in digital integration and theoretical diversity, offering insights for future scholarly directions and strategic HRM practices embedded in quality improvement.